PORTABLE DIAGNOSE IoT DEVICE WITH TWO REACTION CHAMBERS IMPLEMENTATION AND INTEGRATION OF IOT PRINCIPLES ON THE DEVICE. CREATION AND CALIBRATION OF THE LOGICAL FLUX OF THE TWO TESTING CHAMBERS. - Ribeiro, Francisco Emídio (2023)
The Doctor Vida system, a medical solution initially created by STAB VIDA to fight COVID-19, represents a revolutionary integration of advanced medical technology into the healthcare universe. This thesis marks an important milestone in the evolution of this system, focusing on the development and validation of critical components: the newly created Dual DVP device, the associated API of the system, and the mobile application responsible for controlling the IoMT device. At its core, this thesis introduces the design and specification of the Dual DVP device, a remarkable advancement in medical technology. These devices are not only capable of precise temperature control for assays but also exhibit the unique ability to conduct two assays concurrently, all while seamlessly connecting to the Internet and communicating directly with the API and mobile application via the MQTT Internet-based protocol. The development journey extends beyond hardware as it delves into the complexities of firmware and software. The API and mobile application are meticulously designed to integrate the new Dual DVP model into the Doctor Vida ecosystem. This involves redesigning established mechanisms such as pairing, assay creation, data exchange, and real-time assay monitoring. Through rigorous testing, this thesis reveals the system’s capability to consistently and accurately compute assay results. Tests involving Ecoli, RD-Bhyo (B. hyodysenteriae) and COVID-19 assays validate the system’s reliability, mirroring laboratory analysis. As the devices, API, and mobile application validate the development efforts, they open the door to a realm of possibilities. The Doctor Vida system, equipped with these enhancements, is ready for further expansion and feature expansion. This thesis not only confirms the system’s reliability but also ignites new ideas for future applications. In conclusion, this master’s thesis not only showcases technical progresses but also exemplifies the potential for innovative integration of technology in healthcare. The Doctor Vida system represents a step towards smarter, more accessible healthcare, ultimately serving the ever-evolving needs of medical experts and systems.